Genomic predictors of fat mass response to the standardized exercise training - Yang, Xiaolin; Li, Yanchun; Bao, Dapeng; Yan, Bing; Mei, Tao; Liu, Xiaoxi; Cięszczyk, Pawel; Ahmetov, IldusI.; Mc Naughton, LarsRobert; He, Zihong (International Journal of Sports Medicine, 2024)
To explore the genetic architecture underlying exercise-induced fat mass change, we performed a genome-wide association study with a Chinese cohort consisting of 442 physically inactive healthy adults in response to a 12-week exercise training (High-intensity Interval Training or Resistance Training). The inter-individual response showed an exercise-induced fat mass change and ten novel lead SNPs were associated with the response on the level of P<1×10−5. Four of them (rs7187742, rs1467243, rs28629770 and rs10848501) showed a consistent effect direction in the European ancestry. The Polygenic Predictor Score (PPS) derived from ten lead SNPs, sex, baseline body mass and exercise protocols explained 40.3% of the variance in fat mass response, meanwhile importantly the PPS had the greatest contribution. Of note, the subjects whose PPS was lower than −9.301 had the highest response in exercise-induced fat loss. Finally, we highlight a series of pathways and biological processes regarding the fat mass response to exercise, e.g. apelin signaling pathway, insulin secretion pathway and fat cell differentiation biological process.
Keywords: High-intensity interval training; Resistance training; Polygenic Predictor Score; Genome-wide Association Study; Inter-individual Variability